Планировка сел и агропромышленных предприятий - Майборода И. И. Инна Ивановна; Павлышин Б. В. Борис Васильевич; Рогожина Н. В. Наталья Васильевна; Хохол Ю. Ф. Юрий Федорович; Щукина Н. М. Наталья Михайловна (Киев, Будiвельник, 1983)
Авт. указаны на обороте тит. л.